Managing the accuracy and speed of processes for automated monitoring of construction works in the context of new technologies - Artem O. Rada; Aleksandr D. Kuznetsov; Anatoly O. Akulov; Nikolay Yu. Kon’kov (Нанотехнологии в строительстве, 2023)
ABSTRACT: Introduction. Existing automated construction inspection technologies do not allow the user to select the level of detail. At the same time, in the context of the use of nanotechnology, there is a growing need to expand the capabilities of monitoring and control of construction projects. The aim of the research is to develop, implement software, and validate a technology for controlling the speed and accuracy of constructing three-dimensional models from dense point clouds for automated monitoring of construction works. Materials and methods. The research is based on the methodology of non-binary data trees, including the method of constructing octant trees. An unmanned aerial vehicle with an aerial laser scanner, a ground-based scanning total station, and specialized software were used, including the web application “Management System for Monitoring Construction Works on Objects that have undergone state expertise” developed with the participation of the authors. Results and discussion. In the course of the study, a technology was developed and implemented in software that allows the user to select the required balance between accuracy, degree of detail of monitoring and control data for construction work and time costs and computing power requirements. The comparison is made between a construction project, presented in the form of a building information model, and a three-dimensional model of a real object, obtained from a dense point cloud. The degree of comparison accuracy is set by choosing the level of octrees used. By default, the web application uses level eight. However, in the early stages of construction, when the geometric parameters of a dense point cloud deviate significantly from the design boundaries, the ninth, tenth and other levels can be used. In this case, the accuracy and degree of detail increases. Positive and negative deviations are visualized in red and blue colors, respectively, which allows the user to monitor and control the progress of work at the site. Conclusions. The developed technology can be used by customers and other decision makers to control and monitor work.